2003
DOI: 10.1310/rx0a-6e2y-bu8j-w0vl
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Group Intervention for Older Stroke Caregivers

Abstract: Treatment participants showed decreased stress over time but were not significantly different from control participants in the amount of change in stress. Control participants showed a significant increase in burden during the study; treatment participants showed a significant increase in competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 43 publications
4
121
1
7
Order By: Relevance
“…46 King and colleagues 27 reported a significant improvement in caregiver preparedness within a single-group study but found no significant group differences in preparedness in their randomized wait-list control study. 54 Other studies have found significant group differences with respect to caregiver confidence and self-efficacy, 47,48 competence, 49 and by guest on May 10, 2018…”
Section: Survivor Knowledge and Satisfactionmentioning
confidence: 96%
See 3 more Smart Citations
“…46 King and colleagues 27 reported a significant improvement in caregiver preparedness within a single-group study but found no significant group differences in preparedness in their randomized wait-list control study. 54 Other studies have found significant group differences with respect to caregiver confidence and self-efficacy, 47,48 competence, 49 and by guest on May 10, 2018…”
Section: Survivor Knowledge and Satisfactionmentioning
confidence: 96%
“…25,26,29,31,32,34,39,[41][42][43]47,48,52,56,58,59,61,62 15 (46.9) 9 (60) 11 ( Face-to-face and telephone 27,28,30,33,[35][36][37]40,[44][45][46]51,53,54,57,63 13 ( 25,27,28,31,34,36,[40][41][42][43][44][45][46][47][48][49][50]53,…”
Section: Summary and Best-designed Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yapılan girişimlerle, bakım vericilerin depresyon ve stres düzeylerinin azaltılabileceği belirlenmiştir. 23,30,32,35 Bakım vericileri geliştirmek için, kullanılan girişim türlerinden en sık kullanılanı uzaktan eğitim yöntemleridir. Bu amaçla, telefonla danışmanlık ve özel hazırlanmış web sayfaları kullanılmıştır.…”
Section: Yapılan Girişimlerin Etkinliğini Değerlendirme Araçlarıunclassified